Leap motion controller three dimensional verification and polynomial correction. (November 2016) - Curiel-Razo, Yajaira-Ilse; Icasio-Hernández, Octavio; Sepúlveda-Cervantes, Gabriel; Hurtado-Ramos, Juan-Bautista; González-Barbosa, José-Joel
Abstract: We propose a leap motion controller (LMC) dimensional verification based on ISO 10360-2:2009 with a coordinated measuring machine (CMM) as the reference framework. A pointer device comprising a thin aluminum cylinder was used to simulate a human finger. This was mounted on the spindle of the CMM to mark known positions over the LMC workspace. Polynomial tendency line corrections were applied to reduce the error in the LMC and CMM framework alignment. One dimension verification results were less than 0.1 mm in the X and Z axes, whereas the Y axis produced unsuitable results. The mean error was 9.6 mm in three-dimensional (3D) verification. Our findings demonstrate the difference between manufacturer quoted accuracy (0.01 mm) to that practically obtainable when the pointer was placed in a known position. LMC needs to add tracking models and position error compensation in applications requiring high accuracy, such as industrial processes or surgical procedure simulations.